Kesan rawatan haba terhadap mikrostruktur katod berliang Ag2O3-Bi2O3 di atas substrat keluli kalis karat yang disediakan dengan kaedah pengecatan sluri - Dedikarni Panuh; Andanastuti Muchtar; Norhamidi Muhamad; Wan Ramli Wan Daud (Universiti Kebangsaan Malaysia, 2012)
The influence of thermal treatment on the microstructure of Ag2O3-Bi2O3 porous cathode on stainless steel substrates has been investigated. The composite cathode material has been successfully deposited on the substrates by the slurry painting method. The cathode was later thermally treated at different temperatures of 400, 500, 600, 700, 800 and 830oC for 1 h in the atmosphere. Thermal analysis of the dried slurry was conducted in order to determine the heating schedule for eliminating the organic components using thermogravimetry analysis (TGA) and differential scanning calorimetry (DSC). The TGA and DSC analyses confirmed that the organic component was fully decomposed below 418oC, whereas the formation of the composite cathode oxide phases took place at temperatures beyond 600oC. The microstructure of the thermally treated cathode was determined using scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. The SEM results showed that the grain size of the cathode increased with increase in temperature during thermal treatment. The X-ray diffraction (XRD) analyses confirmed the presence of δ-Bi2O3 phase on the cathode. The Ag2O3-Bi2O3 cathode deposited on the stainless steel substrates was found to have a porosity of 53%, 51%, 39% and 28% after 1, 2, 3, and 4 coatings, respectively, and upon thermal treatment at 800°C for 1 h.